Life without Ed : how one woman declared independence from her eating disorder and how you can too - Schaefer, Jenni; Rutledge, Thom (McGraw Hill-Ascent Audio, 2014)
The 10th Anniversary Edition of the book that has given hope and inspiration to thousands who are dealing with eating disorders "If you or someone you love has an eating disorder, this is the book to read." -Dr. Phil Jenni had been in an abusive relationship with Ed for far too long. He controlled Jenni's life, distorted her self-image, and tried to physically harm her throughout their long affair. Then, in therapy, Jenni learned to treat her eating disorder as a relationship, not a condition. By thinking of her eating disorder as a unique personality separate from her own, Jenni was able to break up with Ed once and for all. Inspiring, compassionate, and filled with practical exercises to help you break up with your own personal E.D., Life Without Ed provides hope to the millions of people plagued by eating disorders. Beginning with Jenni's "divorce" from Ed, this supportive, lifesaving book combines a patient's insights and experiences with a therapist's prescriptions for success to help you live a healthier, happier life without Ed. This 10th anniversary edition features a new afterword as well as sections devoted to family, friends, and supporters; how treatment professionals can use the book with their patients; and men with eating disorders. "Of all the great books written on eating disorders, none has had a wider reach than Life Without Ed. Those suffering have found connection and hope, family members have found understanding and empathy, professionals have learned from it and praised it. It will remain a classic for decades to come." -Michael E. Berrett, PhD, psychologist; CEO and cofounder of the Center for Change; coauthor of Spiritual Approaches in the Treatment of Women with Eating Disorders "[Life Without Ed] was the first [book] to teach readers that they can not only separate from their eating disorder, but also disagree with and disobey it. I wholeheartedly recommend this witty, hopeful guide to patients, carers, professionals, and anyone else who wants to understand what it's really like to live with an eating disorder and ultimately triumph over it." -Jennifer J. Thomas, PhD, assistant professor of psychology at the Harvard Medical School; co-director of the Eating Disorders Clinical and Research Program at Massachusetts General Hospital "This uplifting book's intimate inner dialogue has energized countless young women-and men-in their own recoveries from eating disorders." -Leigh Cohn, MAT, CEDS, coauthor of Making Weight: Men's Conflicts with Food, Weight, Shape & Recovery "Jenni is truly a remarkable woman. She unselfishly shares her struggles and triumphs in something that will probably affect all of us in one way or another in our lifetime. Her candid and inspiring story will truly help those suffering from their own "Ed." I feel privileged to know her and her story." -Jamie-Lynn Sigler, actress.